Large-scale Pyrosequencing of synthetic DNA: A comparison with results from Sanger dideoxy sequencing - Gharizadeh, Baback (2006)
Pyrosequencing is a relatively recent method for sequencing short stretches of DNA. Because both Pyrosequencing and Sanger dideoxy sequencing were recently used to characterize and validate DNA molecular barcodes in a large yeast gene-deletion project, a meta-analysis of those data allow an excellent and timely opportunity for evaluating Pyrosequencing against the current gold standard, Sanger dideoxy sequencing. Starting with yeast genomic DNA, parallel PCR amplification methods were used to prepared 4747 short barcode-containing constructs from 6000 Saccharomyces cerevisiae gene-deletion strains. Pyrosequencing was optimized for average read lengths of 25–30 bases, which included in each case a 20-mer barcode sequence. Results were compared with sequence data obtained by the standard Sanger dideoxy chain termination method. In most cases, sequences obtained by Pyrosequencing and Sanger dideoxy sequencing were of comparable accuracy, and the overall rate of failure was similar. The DNA in the barcodes is derived from synthetic oligonucleotide sequences that were inserted into yeast-deletion-strain genomic DNA by homologous recombination and represents the most significant amount of DNA from a synthetic source that has been sequenced to date. Although more automation and quality control measures are needed, Pyrosequencing was shown to be a fast and convenient method for determining short stretches of DNA sequence.